In vivo directed evolution of an ultrafast Rubisco from a semianaerobic environment imparts oxygen resistance - Julie L. McDonald; Nathan P. Shapiro; Amanuella A. Mengiste; Sarah Kaines; Spencer M. Whitney; Robert H. Wilson; Matthew D. Shoulders (Proceedings of the National Academy of Sciences, 2025)
Carbon dioxide (CO 2 ) assimilation by the enzyme Ribulose-1,5-bisphosphate Carboxylase/Oxygenase (Rubisco) underpins biomass accumulation in photosynthetic bacteria and eukaryotes. Despite its pivotal role, Rubisco has a slow carboxylation rate ( k cat CO 2 ) and is competitively inhibited by oxygen (O 2 ). These traits impose limitations on photosynthetic efficiency, making Rubisco a compelling target for improvement. Interest in Form II Rubisco from Gallionellaceae bacteria, which comprise a dimer or hexamer of large subunits, arises from their nearly fivefold higher k cat CO 2 than the average Rubisco enzyme. As well as having a fast k cat CO 2 (25.8 s − 1 at 25 °C), we show that Gallionellaceae Rubisco (GWS1B) is extremely sensitive to O 2 inhibition, consistent with its evolution under semianaerobic environments. We therefore used an in vivo mutagenesis-mediated screening pipeline to evolve GWS1B over six rounds under oxygenic selection, identifying three catalytic point mutants with improved ambient carboxylation efficiency: Thr-29-Ala (T29A), Glu-40-Lys (E40K), and Arg-337-Cys (R337C). Full kinetic characterization showed that each substitution enhanced the CO 2 affinity of GWS1B under oxygenic conditions by subduing oxygen affinity, leading to 25% (E40K), 11% (T29A), and 8% (R337C) enhancements in carboxylation efficiency under ambient O 2 at 25 °C. By contrast, under the near anaerobic natural environment of Gallionellaceae , the carboxylation efficiency of each mutant was impaired ~16%. These findings demonstrate the efficacy of artificial directed evolution to access distinctive regions of catalytic space in Rubisco.